A Pilot Pre and Post 4 Week Intervention Evaluating the Effect of a Proprietary, Powdered, Plant Based Food on Micronutrient Status, Dietary Intake, and Markers of Health in a Healthy Adult Population - Wilcox, Matthew D.; Chater, Peter I.; Stanforth, Kyle J.; Williams, Rebecca; Brownlee, Iain A.; Pearson, Jeffrey P. (Frontiers in Nutrition, 2022)
Background A ‘balanced, adequate and varied diet’ is recommended as the basis of nutritional diet by the World Health Organization and national public health agencies. Huel is a proprietary, on-the-go, powdered, plant based food, providing all 26 essential vitamins and minerals, protein, essential fats, carbohydrate, fibre, and phytonutrients. Objectives Assessing the effect of solely consuming Huel on micronutrient status, dietary intake and markers of health was achieved through a 4-week intervention of solely Huel powder. Methods Normal energy intake was assessed through a one-week lead in period with healthy adult participants (aged 18 or over) logging their food intake, after which only Huel was consumed for 4 weeks. Blood samples and body composition was assessed before and after the lead in week as well the end of the intervention. 30 participants were recruited with 20 (11 females, median age 31, range 22-44) completing the study, 19 sets of blood samples were collected. 21 blood markers were analysed along with weight, BMI, waist circumference, visceral adipose tissue (VAT), and body composition. All blood micronutrients, except for Thyroid Stimulating Hormone and Choline were sent to Royal Victoria Infirmary NHS, Newcastle Laboratory (Newcastle, UK) for analysis. Results 14 of the parameters significantly changed over the course of the study with circulating haemoglobin, iron, vitamins B12 and D as well as selenium significantly increasing (p<0.05). HbA1c, total and non-HDL cholesterol, vitamins A and E, potassium, BMI, VAT, and waist circumference all significantly decreased (p<0.05) post intervention. Conclusions Although energy intake decreased during the intervention period, the adherence to recommended micronutrient intake, as quantified by the dietary Total Adherence Score, significantly increased which tallies with the preservation or improvement of micronutrient status. This study potentially demonstrates that consuming only Huel for 4 weeks does not negatively affect micronutrient status.